Capped Fluorescent Carbon Dots for Detection of Hemin: Role of Number of –OH Groups of Capping Agent in Fluorescence Quenching - Upama Baruah; Neelam Gogoi; Gitanjali Majumdar; Devasish Chowdhury (The Scientific World Journal)
We have successfully demonstrated the use of capped carbon dot systems, namely, CDs/β-cd, CDs/LMH, and CDs/Suc, as fluorescent sensors for the detection of hemin. The capped carbon dot systems showed quenching of PL intensity in the presence of hemin. The minimum detection limit was determined to be ~1 μM. The PL response with free Fe(II) and Fe(III) was also studied. It was observed that PL quenching of capped carbon dot systems in the presence of hemin is dependent on the number of –OH groups in the capping agent. The order of quenching towards hemin was determined to be CDs/β-cd > CDs/LMH = CDs/Suc > CDs. A possible mechanism to account for the observation is also discussed in the paper.